Pemberian Kombinasi Buah Alpukat (Persea americana) dan Rebusan Air Daun Salam (Syzygium polyanthum) Terhadap Penurunan Tekanan Darah pada Pasien Hipertensi - Wanda Millenia Alwie; Nur Masyithah; Hadi Kuncoro (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Avocado and bay leaves contain flavonoids which can have an effect on lowering blood pressure. This study aims to determine the characteristics of hypertension patient respondents including age, gender, education, occupation, family history and antihypertensive drugs consumed and to determine the effect of giving a combination of avocado juice and bay leaf water boiled in Samarinda Ulu District. The research method used was a quasi-experimental design and research procedures by measuring before and after treatment. The collection of data on the characteristics of respondents obtained the highest percentage is the category of female gender as much as 67%, age 56-60 years as much as 42%, elementary education as much as 33%, work housewife 58%, having a family history of 75 % and the antihypertensive drug that was consumed by amlodipine was 100%. The results of data analysis using the independent sample T test showed that the p-value for the control-treatment systolic group and the control-treatment diastolic group was 0.000 (p-value